The theory and practice of measure in medieval polyphony to the ars nova - Bonge, Dale Jay (Michigan University microfilms international, 1984)
A Dissertation submitted for the fulfillment of the requirements for the degree of Dostor in the Philosophy (Music: Musicology) in The University of Michigan 1975